ANÁLISE DA POSSIBILIDADE DE REDUÇÃO DA JORNADA DE TRABALHO SEM PREJUÍZO SALARIAL AOS EMPREGADOS DA INICIATIVA PRIVADA QUE TENHAM SOB SEUS CUIDADOS PESSOA COM DEFICIÊNCIA (REMUNOM, 2023)
This article analyzes the possibility of granting a reduction in working hours without prejudice to wages for at least one of the people responsible for caring for a disabled person, be they a child, spouse or dependent. The object of study is employees in the private sector, whose legal regime is that contained in Decree-Law No. 5,452 of May 1, 1943 (Consolidation of Labor Laws). The aim of the research is to analyze the possibility of applying reduced working hours to private employees governed by the CLT in a similar way to that already applied to civil servants of the Federal Government, federal agencies and public foundations, as well as state and municipal civil servants, under the terms of the legislation in force and the jurisprudential understanding emanating from the Federal Supreme Court on the subject. Through bibliographical, legal and jurisprudential research, it was noted that the Superior Labor Court has not yet dealt exhaustively with the issue, but, to a certain extent, has favorable judgments only in very specific cases, of public employees, so that the lack of legislation on the subject makes it difficult to reach a definitive conclusion on the possibility of reducing working hours without prejudice to wages for employees of the private sector.Keywords: Working Hours; Responsible; Consolidation of Labor Laws; Person with Disabilities